Sistem Pendudkung Keputusan Manajemen Data Beasiswa Pada Biro Administrasi Akademik Kemahasiswaan Universitas Tribuana Kalabahi - Erna J. Malaikosa (Peneliti.net, 2021)
The provision of scholarships to students is an effort by universities to increase community participation and also encourage students to continue to participate. Determination of scholarship recipients is still done manually, resulting in scattered scholarship data management. The purpose of this research was to create a system that could help expedite the process of data management based on the type of category in each study program quickly and objectively. The method used in this research is Simple Additive Weighting (SAW) with data analysis techniques UML (Unified Modeling Language). This system was successfully built in the form of an application for the Tribuana Kalabahi University Scholarship Award Decision Support System based on the terms and criteria specified at the Tribuana Kalabahi University Student Administration Bureau. The resulting application can be used to determine eligible scholarship recipients objectively based on established criteria and also to record data on the types of scholarships received by students in each study program.